2021
DOI: 10.3390/jof7121082
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Assembly Processes of Soil Fungal Communities along an Altitudinal Gradient in Tibetan Plateau

Abstract: In soil ecosystems, fungi exhibit diverse biodiversity and play an essential role in soil biogeochemical cycling. Fungal diversity and assembly processes across soil strata along altitudinal gradients are still unclear. In this study, we investigated the structure and abundance of soil fungal communities among soil strata and elevational gradients on the Tibetan Plateau using Illumina MiSeq sequencing of internal transcribed spacer1 (ITS1). The contribution of neutral and niche ecological processes were quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 116 publications
2
13
0
Order By: Relevance
“…The community composition of soil fungi (total and trophic modes) changed significantly in different vegetation types, which reflected the response of the soil fungal community composition to altitude in the alpine–gorge region ( Figure 2 and Figure 3 ). Ascomycota, Basidiomycota, and Mortierellomycota were the top three dominant phyla of soil fungal communities in the region ( Figure 2 a), which was similar to findings on the southeastern Qinghai–Tibetan Plateau [ 42 ]. Along the altitude gradient, the other 11 phyla of soil fungi in subalpine coniferous forests (E5) comprised the smallest proportion, accounting for only 1.44%, followed by subalpine broadleaf mixed forest (E3), accounting for 2.36% ( Figure 2 a).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The community composition of soil fungi (total and trophic modes) changed significantly in different vegetation types, which reflected the response of the soil fungal community composition to altitude in the alpine–gorge region ( Figure 2 and Figure 3 ). Ascomycota, Basidiomycota, and Mortierellomycota were the top three dominant phyla of soil fungal communities in the region ( Figure 2 a), which was similar to findings on the southeastern Qinghai–Tibetan Plateau [ 42 ]. Along the altitude gradient, the other 11 phyla of soil fungi in subalpine coniferous forests (E5) comprised the smallest proportion, accounting for only 1.44%, followed by subalpine broadleaf mixed forest (E3), accounting for 2.36% ( Figure 2 a).…”
Section: Discussionsupporting
confidence: 84%
“…Some studies have also showed that soil total nitrogen and nitrate nitrogen are the key drivers for α-diversity of saprophytic and pathogenic fungi along altitude gradients, respectively [ 41 ]. The β-diversity of soil fungi was found to be driven by environmental factors, geographic distance, or their combination along altitude gradients [ 42 , 43 , 44 ]. The driver divergence of turnover and nestedness components of soil fungal β-diversity has been validated at regional scales [ 30 ], but it has not been validated along altitude gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, these experiments also showed that in the case of fungi, the effect of the host species has a stronger force in the acquisition of the fungal communities in the rhizosphere from soil ( Hannula et al, 2019 ; Thiergart et al, 2020 ). It is important to note that in the case of fungi, various studies point to the existence of stochastic factors that randomly determine the assembly of fungal communities in the rhizosphere, the main one being the dispersal ability of fungi in the soil ( Hussain et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these deterministic factors, soil microbial communities can also be affected by stochastic processes that generate species compositional patterns indistinguishable from those produced at random ( Tripathi et al, 2018 ; Richter-Heitmann et al, 2020 ; Hussain et al, 2021 ; Zhang et al, 2021 ). These stochastic processes involve random proliferation, death, and dispersal events ( Tripathi et al, 2018 ; Richter-Heitmann et al, 2020 ; Hussain et al, 2021 ; Zhang et al, 2021 ). Then, the ratio between stochastic and deterministic effects on microbial communities affects the species diversity and composition over temporal and spatial scales ( Tripathi et al, 2018 ; Richter-Heitmann et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation